THE ROLE PERCEPTION OF FEMALE SECONDARY SCHOOL ADMINISTRATORS IN EKITI STATE - Oluremi, Olaleye Florence (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2016)
This study examined the self perceived role of female administrators of secondary schools in Ekiti State, Nigeria. Such perception is based on performing specific tasks, and is compared to the role of female administrators as perceived by the teachers under them and the board members of the Teaching Service Commission. A purposive sampling technique was used to select thirty (30) female principals/administrators, 670 teachers under them and five Board members. A 40 item questionnaire, arranged in a summated rating Likert Whitney U-test was employed to test the significance difference between the self-perceived role of female administrators and their role as perceived by both the teachers and Board member. Findings showed that self-perceived role of the female secondary school administrators is significantly different from her role as perceived by the teachers under them in (1) Staff Development (2) Instructional Supervision and (3) Finance and Budgeting Whereas both the female administrators and their superordinates (Board members) perceived the role of the female administrators in the following order of importance. 1. Staff development 2. Finance and Budgeting 3. Community Relations 4. Instructional Supervision 5. Student welfare Services. It was recommended that both male and female school administrators need some orientation courses on professional matters regularly.